2003
DOI: 10.1074/jbc.m302804200
|View full text |Cite
|
Sign up to set email alerts
|

FoxO6, a Novel Member of the FoxO Class of Transcription Factors with Distinct Shuttling Dynamics

Abstract: Forkhead transcription factors of the FoxO-group are associated with cellular processes like cell cycle progression and DNA-repair. FoxO function is regulated by protein kinase B (PKB) via the phosphatidylinositol 3-kinase/PKB survival pathway. Phosphorylation of serine and threonine residues in specific PKB phosphorylation motifs leads to exclusion of FoxO-proteins from the nucleus, which excludes them from exerting transactivating activity. Members of the FoxO-group have three highly conserved regions contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
263
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 315 publications
(272 citation statements)
references
References 26 publications
7
263
1
1
Order By: Relevance
“…FOXO1, FOXO3, and FOXO4 are highly related, share the same DNA‐binding motifs, present similar patterns of expression, and seem to have overlapping functions (Anderson et al ., 1998; Biggs et al ., 2001; Jacobs et al ., 2003; Obsil & Obsilova, 2011). FOXO6 is mainly expressed in the brain and has been shown to be regulated by distinct mechanisms.…”
Section: Animal Modelsmentioning
confidence: 99%
“…FOXO1, FOXO3, and FOXO4 are highly related, share the same DNA‐binding motifs, present similar patterns of expression, and seem to have overlapping functions (Anderson et al ., 1998; Biggs et al ., 2001; Jacobs et al ., 2003; Obsil & Obsilova, 2011). FOXO6 is mainly expressed in the brain and has been shown to be regulated by distinct mechanisms.…”
Section: Animal Modelsmentioning
confidence: 99%
“…In mammalian species, the FOXO subfamily includes FOXO1, FOXO3, FOXO4 and FOXO6. FOXO1, FOXO3 and FOXO4 are widely expressed in various tissues and organs (8), however the expression of FOXO6 is most often detected in the developing brain (9), and recent studies have demonstrated that FOXO6 is involved in cell growth and transformation of liver cancer and lung cancer (10,11). FOXO homolog genes, DAF-16 and dFOXO, exists in lower organisms, including Caenorhabditis elegans, Drosophila and sponges (12).…”
Section: Introductionmentioning
confidence: 99%
“…The PI3K-PKB signalling cascade is a key pathway by which cells may respond to a wide range of stimuli, which may be generated intrinsically (for example, growth factors, cytokines and cell-cell contact) or from an external source (for example, irradiation, and physical or genotoxic stress) (Leevers et al, 1999;Hennessy et al, 2005;Wymann and Marone, 2005;Samuels and Ericson, 2006). At the molecular level, many of the PI3K-PKB-mediated mitogenic responses are achieved through the direct repression of FoxO transcription factors by PKB-mediated phosphorylation, promoting nuclear export, proteosomal degradation and a decrease in transactivation activity (Brunet et al, 1999(Brunet et al, , 2001Kops et al, 2002b;Jacobs et al, 2003). FoxO is also a target of many other kinases, including serum and glucocorticoid-regulated kinase, c-Jun N-terminal kinase, a dual specificity tyrosinephosphorylated and regulated kinase (DYRK1A), CDK2 and IkB kinase (Brunet et al, 1999(Brunet et al, , 2001Kops et al, 2002b;Jacobs et al, 2003;Greer and Brunet, 2005) and the deregulation of PKB and these kinases is frequently observed in proliferative disorders and can contribute significantly to tumorigenesis (Hennessy et al, 2005;Samuels and Ericson, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…At the molecular level, many of the PI3K-PKB-mediated mitogenic responses are achieved through the direct repression of FoxO transcription factors by PKB-mediated phosphorylation, promoting nuclear export, proteosomal degradation and a decrease in transactivation activity (Brunet et al, 1999(Brunet et al, , 2001Kops et al, 2002b;Jacobs et al, 2003). FoxO is also a target of many other kinases, including serum and glucocorticoid-regulated kinase, c-Jun N-terminal kinase, a dual specificity tyrosinephosphorylated and regulated kinase (DYRK1A), CDK2 and IkB kinase (Brunet et al, 1999(Brunet et al, , 2001Kops et al, 2002b;Jacobs et al, 2003;Greer and Brunet, 2005) and the deregulation of PKB and these kinases is frequently observed in proliferative disorders and can contribute significantly to tumorigenesis (Hennessy et al, 2005;Samuels and Ericson, 2006). The intimate link between FoxO signalling and regulation of cell cycle control is highlighted by the fact that in these instances the re-introduction of FoxO expression, for example in PTEN-deficient tumours, can induce cell cycle arrest followed by cell death (Nakamura et al, 2000).…”
Section: Introductionmentioning
confidence: 99%